(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The rapid growth of motor vehicles in India has significantly increased the number of road accidents and compensation claims arising from them. The traditional adjudicatory process before Motor Accident Claims Tribunals (MACTs) often suffers from delays, procedural complexities, and prolonged litigation, thereby depriving victims and their families of timely relief. In this context, Alternative Dispute Resolution (ADR) mechanisms have emerged as an effective means of resolving motor accident compensation disputes in a speedy, economical, and amicable manner. ADR methods such as Lok Adalats, mediation, conciliation, arbitration, and negotiated settlements have increasingly become important tools in ensuring access to justice and reducing judicial burden. The present article critically examines the role of ADR in settlement of motor accident compensation claims in India. It explores the statutory framework under the Motor Vehicles Act, 1988 and the Legal Services Authorities Act, 1987, analyzes judicial approaches encouraging ADR in compensation disputes, and evaluates the contribution of Lok Adalats and mediation centres in achieving timely compensation for victims. The study further discusses the advantages of ADR, including speedy disposal, reduced litigation costs, flexible procedures, and reduction of pendency before MACTs. Simultaneously, it identifies major challenges such as unequal bargaining power, inadequate compensation, lack of legal awareness, and institutional limitations. The article concludes that ADR mechanisms have become indispensable for efficient disposal of motor accident compensation claims in India. However, reforms relating to transparency, victim-centric approaches, digital infrastructure, and standardized settlement mechanisms are necessary for ensuring fairness and effectiveness in ADR proceedings.